In Vitro Effect of p-Chlormercuribenzoate upon Dilute Blood Clot Lysis Time in Hyperlipemia - Cucuianu, Mircea P; Stef, Codruta; Zdrenghea, Dorel; Popescu, Octavian (Thrombosis and Haemostasis, 1979)
In comparison to values obtained in normal-weight normolipenic controls, dilute blood clot lysis time was found to be prolonged in resting and exercised patients with endogenous hypertriglyceridemia. Lysis time was also prolonged in overweight subjects with only slightly increased serum lipids but it was not significantly changed in type II-a hyperlipoproteinemia. An obvious acceleration of clot lysis was noted in patients with decompensated cirrhosis of the liver. Inclusion of p-chlormercuribenzoate (PCMB) into the diluted blood clot caused an acceleration of lysis time. This effect was particularly obvious with hypertriglyceridemic blood and minimal with blood obtained from cirrhotic patients. Addition of various amounts of heat-defibrinated plasma to blood from cirrhotic patients caused a proportional prolongation of clot lysis time and this effect was greatly diminished in the presence of PCMB. Similar amounts of serum had a much lesser effect than defibrinated plasma. Inhibition of fibrin cross-linking by PCMB was confirmed by sodium dodecylsulfate polyacrylamide gel electrophoresis.The present data complete previous observations concerning a higher plasma factor XIII activity in type II-b and type IV hyperlipoproteinemia and suggest that an increased crosslinking of fibrin might partially explain the deficient thrombolysis of hypertriglyceridemic patients.